Innovative Design for Movement Scheme of Mechanical System based on the TRIZ and FAHP - Qu Shuwei; Li Ruiqin; Guo Zhihong (Jixie chuandong)
The mechanical system movement scheme design and selection is the key step in the design of mechanical system. The method for innovative design of mechanical system is proposed based on TRIZ（ Theory of inventive problem solving） and FAHP（ Fuzzy analytic hierarchy process）. According to the mechanical system performance index,the correlation matrix of the performance index and the engineering parameters of TRIZ are constructed. The solving procedure of conflict matrix of mechanical system is proposed. Aiming at the fuzziness and uncertainty of the mechanical system movement scheme evaluation,through constructing the fuzzy membership functions to select and evaluate,The validity of the method is verified by an example.